The energy efficiency of a country under the Green Deal Policy: the causal relationship between key determinants - Pimonenko, Tetyana (<center>Conference Proceedings Determinants Of Regional Development</center>; No 2 (2021): Conference Proceedings - VIII International Scientific Conference Determinants of Regional DevelopmentDO - 10.14595/CP/02/005, 2021)
The paper aimed to check the impact of the core determinants on a country's energy efficiency policy. At the first stage of the investigation, the bibliometric analysis was used. It allowed identifying the determinants analysed by the scientists under the estimation of the country's energy efficiency policy. Thus, the following indicators were allocated: green investment; greenhouse gas emissions; share of the renewable energy in the final energy consumption. The study used the indicator energy efficiency for estimating energy efficiency policy of the country. The study used the bibliometrics analysis with instruments as follows as: Scopus and Web of Science Analysis Tools (to analyse the general tendency of publication activities); VOSviewer (to visualise the findings of meta-analysis); SciVal (for collaboration analysis). For the checking of the casual relationships between selected indicators, the following methods were applied: panel unit root test, Pedroni panel cointegration tests, the fully modified ordinary least squares (FMOLS) and dynamic ordinary least squares (DOLS) panel cointegration techniques, Granger causality test. The data from the following databases were used: the Eurostat, Ukrstat and the European Environmental Agency. The findings confirmed the bi-directional causality between energy efficiency and renewable energy, unidirectional causality from greenhouse gas emissions to energy efficiency. Besides, considering the results of cointegration analysis, increasing the share of renewable energy in the final energy consumption provoked: the increasing the energy efficiency by 46% (FMOLS) and 32% (DOLS). The increasing of greenhouse gas emissions by 1% initiated declining of energy efficiency by 16% (FMOLS) and 28% (DOLS); growing of green investment by 1% allowed the increasing of energy efficiency of the country by 71% (FMOLS) and 72% (DOLS). In this case, the government should implement effective instruments and policies to decline air pollution. Thus, under the transition process to the carbon-free economy, the additional green investment for renewable energy and green technologies reduces greenhouse gas emissions.